2020
DOI: 10.3390/biom10010158
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Migratory and Pro-Apoptotic Properties of Parvifloron D on Triple-Negative Breast Cancer Cells

Abstract: Medicinal plants are important sources of new bioactive compounds with potential anticancer activity. Parvifloron D (ParvD) is an abietane diterpenoid, isolated in high amounts from Plectranthus ecklonii Benth. Previous reports have suggested potential therapeutic properties for ParvD. ParvD has shown pro-apoptotic and cytotoxic effects in leukemia and melanoma cell lines. However, to the best of our knowledge, there are no studies in triple-negative breast cancer (TNBC) models. TNBC is a breast cancer subtype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…Our previous study showed a stronger cytotoxic effect for Parv (IC 50 = 3.125 µg/mL) compared to Roy (IC 50 = 25 µg/mL) against primary H7PX glioma cells [12]. A similar effect was shown by Saraiva et al [16] for Parv for human breast cancer (MDA-MB-231) cells with IC 50 = 2.48 µM. Additionally, Parv also demonstrated promising cytotoxic activity against human leukemia (HL-60, MOLT-3, K562, and U937) [10] and melanoma (human A375 and mouse B16VP) [11] cell lines.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Our previous study showed a stronger cytotoxic effect for Parv (IC 50 = 3.125 µg/mL) compared to Roy (IC 50 = 25 µg/mL) against primary H7PX glioma cells [12]. A similar effect was shown by Saraiva et al [16] for Parv for human breast cancer (MDA-MB-231) cells with IC 50 = 2.48 µM. Additionally, Parv also demonstrated promising cytotoxic activity against human leukemia (HL-60, MOLT-3, K562, and U937) [10] and melanoma (human A375 and mouse B16VP) [11] cell lines.…”
Section: Discussionsupporting
confidence: 76%
“…The WHO lists cancers such as leukemia and lung cancer as the second leading cause of death globally, accounting for an estimated 9.6 million deaths, i.e., one in six, in 2018 [22]. A wide range of active abietane diterpenes with various medical activities can be obtained from species of Plectranthus [13][14][15][16], a large and widespread genus with a diversity of ethnobotanical uses [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arguably, the most important class of chemicals produced by the Lamiaceae family is the terpenoids; of these, the most numerous subclass of compounds with confirmed anticancer properties is that of the diterpenoids. Many possess pro-apoptotic properties, including 3-acetoxylteuvincenone from Ajuga ovalifolia whole plants [ 263 ], sahandone and sahandol II from Salvia chloroleuca roots [ 264 ], acetyl-macrocalin B from Isodon sylvatica [ 265 ], parvifloron D from Plectranthu ecklonii [ 227 ], and 7β-acetoxy-20-hydroxy-19,20-epoxyroyleanone from Salvia corrugate shoots [ 266 ]. 3-acetoxylteuvincenone activates Src homology phosphotyrosine phosphatase 2 (SHP2) and induces extracellular signal-regulated kinase (ERK) 1/2 and Akt pathways in A549 cells [ 263 ].…”
Section: The Lamiaceae Family Plantsmentioning
confidence: 99%
“…Cdc25C phosphatase dephosphorylates the cyclin B-CDK1 complex and enables cell entry into mitosis but inactivates it, preventing cell cycle progression [ 270 ]. Another diterpenoid, parvifloron D, induces apoptotic morphological changes in MDA-MB-231 cells [ 227 ]. 7β-acetoxy-20-hydroxy-19,20-epoxyroyleanone promotes G0/G1 cell cycle delay and ROS activation of ERK1/2 kinase in human breast cancer SKBR-3 and human breast carcinoma BT474 cell lines [ 266 ].…”
Section: The Lamiaceae Family Plantsmentioning
confidence: 99%